STUDY TRAINING AS MEANS OF FUTURE SPECIALISTS IN PHYSICAL CULTURE AND SPORT COMMUNICATIVE COMPETENCE CREATING - Beseda, Nataliia; Vorobjov, Oleksiy (Educological discourse, 2018)
Theoretical and practical experience referring communicative competence defining as a significant component of specialist’s professional development is systematized in the article. Thereupon it is defined that developing future specialists in physical education and sport effective communicative abilities is becoming especially important in the process of their professional training. Purposefulness of implementing organizational and pedagogic conditions for increasing specialist’s readiness for professional activity is grounded. They include the following ones: improving training essence, forms and methods; growth of students’ value-based attitude to professional activity; developing their commitment to self-development and professional advancement. The purpose of the article is to analyze peculiarities of developing future specialists in physical education and sport communicative competence in the process of training lesson. Special aspects of developing future specialists in physical education and sport communicative competence in the process of training lesson are characterized. Training is proved to be a technology oriented towards group work organizing and at the same time at developing each training group’s member personality. The essence of pedagogic communication, its functions and styles are revealed. Communicative barriers and approaches to their elimination are defined and characterized. Exercises aimed at developing students’ functional communication, active listening and effective cooperation with surrounding people are suggested. Situational tasks modeling future professional activity are chosen. Their performing contributes to mastering “I-statement” technique.